2018
DOI: 10.1186/s12014-018-9192-2
|View full text |Cite
|
Sign up to set email alerts
|

The response to neoadjuvant chemoradiotherapy with 5-fluorouracil in locally advanced rectal cancer patients: a predictive proteomic signature

Abstract: BackgroundColorectal cancer is the third most common and the fourth most lethal cancer in the world. In the majority of cases, patients are diagnosed at an advanced stage or even metastatic, thus explaining the high mortality. The standard treatment for patients with locally advanced non-metastatic rectal cancer is neoadjuvant radio-chemotherapy (NRCT) with 5-fluorouracil (5-FU) followed by surgery, but the resistance rate to this treatment remains high with approximately 30% of non-responders. The lack of evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 56 publications
(57 reference statements)
4
40
0
Order By: Relevance
“…Moreover, CALD1 encodes the caldesmon protein, which is a calmodulin-binding and cytoskeleton-associated protein and regulates cell motility, such as migration and invasion (40,41). It has been suggested that CALD1 may indicate a general splicing event associated with cancer (41,42) and was also identified as a potential prognostic molecular marker for bladder and colon cancer (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CALD1 encodes the caldesmon protein, which is a calmodulin-binding and cytoskeleton-associated protein and regulates cell motility, such as migration and invasion (40,41). It has been suggested that CALD1 may indicate a general splicing event associated with cancer (41,42) and was also identified as a potential prognostic molecular marker for bladder and colon cancer (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Previous mass spectrometric proteomic studies that have analyzed the proteome of cancer patients receiving radiotherapy have to a large extent focused on attempts to identify proteins that could be used as biomarkers to guide the use of radiotherapy by predicting patient response [10,11]. Several studies involving the proteomic profiling of rectal cancer patients have also identified proteins implicated in resistance to radiotherapy, such as acid ceramidase, or protein signatures predictive of radiotherapy response [12][13][14][15][16]. However, there is a paucity of studies with focus on investigating the overall effects of radiotherapy on plasma protein expression in rectal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with lung adenocarcinoma who have up-regulated ACTA2 expression are more likely to develop distant metastasis and have detrimental prognosis [32]. Besides, the expression level of CALD1 is higher in patients with rectal cancer who do not respond to the neoadjuvant radiochemotherapy [33]. Blockade of MYL9 function is a critical factor for reducing the matrix-remodelling and invasion-promoting abilities of cancer-associated broblasts [34].…”
Section: Discussionmentioning
confidence: 99%